2015
DOI: 10.2485/jhtb.24.397
|View full text |Cite
|
Sign up to set email alerts
|

Pathological Examination of Experimentally Induced Periodontal Polyp in Mice

Abstract: : The mechanism in the formation of periodontal polyp has been established in several histological studies but details on cell differentiation and/or proliferation have not been elucidated. In the present study, we established a convenient and possible experimental system using ddY mice. Briefly, pentobarbital sodium (Somnopentyl) was injected into the abdominal cavity of the mouse followed by access cavity preparation on maxillary first molar using low speed ½ round bur (Merufa Inc), exposing the pulp and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 9 publications
1
6
0
Order By: Relevance
“…Experimental perforation of floor of the dental pulp in mice caused a slight initial suppurative inflammation leading to granulation tissue growth due to gradual chronic inflammation. Similar results were observed from previous experiment 1 .…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Experimental perforation of floor of the dental pulp in mice caused a slight initial suppurative inflammation leading to granulation tissue growth due to gradual chronic inflammation. Similar results were observed from previous experiment 1 .…”
Section: Discussionsupporting
confidence: 92%
“…These problems tend to be more when treating deciduous teeth in clinical pediatric dentistry. The consequence of a large perforation is chronic inflammatory hyperplasia 1 . Granulation tissue grows in the periodontal ligament from the perforated dentin causing periodontal polyp, which may also grow into the pulp cavity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kaneko et al also reported the differentiation of BMDCs into cell components of periodontal tissue [14]. In our study, the method suggested by Osuga et al [22] was used for the formation of granulation tissue through chronic inflammation in the dental pulp of GFP bone marrow transplanted mice [16]. Observations by micro-computed tomography (m-CT) [23,24], histopathology, and immunohistochemistry were followed over time.…”
Section: Recruitment Of Bmdcs To Periodontal Tissue and Dental Pulpmentioning
confidence: 89%
“…When the tooth crown is destroyed by caries, the pulp cavity is perforated. High proliferative activity of the pulpal tissue results in chronic inflammatory hyperplasia [16]. Granulation tissue grows from the pulp and forms periodontal polyps that can grow from inside the pulp cavity to outside the pulp.…”
Section: Recruitment Of Bmdcs To Periodontal Tissue and Dental Pulpmentioning
confidence: 99%